[45] Role of nephrometry scoring systems (R.E.N.A.L.-PADUA) in planning nephron-sparing surgery in patients with renal masses: Retrospective study of 88 cases - Abdelkrim Boulatrous (Taylor & Francis Group, 2018)
Objective: To assess the utility of nephrometry scoring systems (R.E.N.A.L.-PADUA) in planning nephron-sparing surgery (NSS) in patients with renal masses. NSS has become the standard for the management of localised renal masses; however, an objective preoperative evaluation is needed. The nephrometry scores role is preoperative evaluation of the complexity of partial nephrectomy (PN) and evaluation of possible postoperative complications, and these scores are not yet standardly used in many countries including Algeria. Methods: We retrospectively evaluated the clinical records of patients who underwent surgical treatment of renal masses between 2013 and 2016 for clinical renal tumours in the Urology Department of Annaba University Hospital, Algeria. All patients underwent preoperative computed tomography or magnetic resonance imaging to define the clinical stage and anatomical characteristics of the tumours. PADUA and R.E.N.A.L. scores were retrospectively assessed for each of the 88 patients. Uni- and multivariate analyses were used to evaluate the correlations between age, gender, Charlson Comorbidity Index, clinical tumour size, PADUA and R.E.N.A.L. complexity group categories, and grade of postoperative complications. Results: We noticed that only nine patients had NSS and all the others a total nephrectomy; however, 20 of them had a moderate complexity score for PN and seven a low complexity score. Then we compared with the results with the management in 2017 and 2018, the attitude was more liberal with the number of PNs greater than that of the 6 years previously. Conclusion: A precise stratification of patients with both PADUA and R.E.N.A.L before nephrectomy is recommended to consider the potential threats and benefits of NSS. They are valuable tools to categorise renal tumours based on anatomical features and to prevent patients from abusive total nephrectomies conserving significant nephronic capital.